2012
DOI: 10.1261/rna.036269.112
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of quaternary structure and enhancement of ligand binding by the K-turn of tandem glycine riboswitches

Abstract: Most known glycine riboswitches have two homologous aptamer domains arranged in tandem and separated by a short linker. The two aptamers associate through reciprocal "quaternary" interactions that have been proposed to result in cooperative glycine binding. Recently, the interaptamer linker was found to form helix P0 with a previously unrecognized segment 5′ to the first aptamer domain. P0 was shown to increase glycine affinity, abolish cooperativity, and conform to the K-turn motif consensus. We examine the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 46 publications
8
46
1
Order By: Relevance
“…This analysis was enabled by the inclusion of the leader, which allows the riboswitch to behave well at higher RNA concentrations. We confirmed that wildtype (WT) VC1-2 containing the leader sequence binds glycine noncooperatively with low micromolar affinity, in agreement with other recent reports (Kladwang et al 2012;Sherman et al 2012;Baird and Ferré-D'Amaré 2013). Because the inclusion of the leader sequence dramatically changes the ligand-binding activity of the riboswitch, we wished to verify if each ligand-binding site in the tandem riboswitch with leader binds to a separate molecule of glycine.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…This analysis was enabled by the inclusion of the leader, which allows the riboswitch to behave well at higher RNA concentrations. We confirmed that wildtype (WT) VC1-2 containing the leader sequence binds glycine noncooperatively with low micromolar affinity, in agreement with other recent reports (Kladwang et al 2012;Sherman et al 2012;Baird and Ferré-D'Amaré 2013). Because the inclusion of the leader sequence dramatically changes the ligand-binding activity of the riboswitch, we wished to verify if each ligand-binding site in the tandem riboswitch with leader binds to a separate molecule of glycine.…”
Section: Resultssupporting
confidence: 90%
“…At RNA concentrations ∼30 times the K d , the WT tandem riboswitch containing the leader sequence binds 1.8 equivalents of glycine (Table 1), in agreement with the original studies on the glycine riboswitch, but in contrast to the recent report of a single equivalent bound as reported using isothermal titration calorimetry (ITC) (Baird and Ferré-D'Amaré 2013). The disparity might arise from a variety of differences between the techniques, including longer equilibration times or refolding the riboswitch in the presence of the ligand.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…When in water only, RNA is expected to be unstructured, and W-band spectrum ( Figure 4C top and S8) with a SNR value of 18:1 reveal disorder, with spectral simulation giving a correlation time of 0.4 ns. It has previously been shown that, upon addition of salts and ligands, the VC glycine riboswitch folds with formation of the kink turn [53,54,63,64] where, based upon comparisons to X-ray models of other k-turn motifs [65,66], the modified U2-base is expected to become base paired/base stacked. Hence, a decrease in dynamics (an increase in correlation time) is anticipated.…”
Section: Characterizing Conformational Dynamics In Large Rnasmentioning
confidence: 99%